Empirical Factors of Takliq Talaq Through Electronic Media in View of Positive Law And Islamic Law - Ahdiyatul Hidayah; Rif’an Syafruddin; Ergina Faralita; Faturrahman Fahrozi; Ahmad Rifani (Syariah: Jurnal Hukum dan Pemikiran, 2023)
The words talaq are usually expressed verbally or directly by the husband to his wife, so that the wife can directly hear the expression of the word divorce from her husband. But along with the era of globalization, communication media in the form of cellphones turned out to be used by some husbands who were disappointed with their wives as a medium to declare divorce. The phenomenon of talaq through electronic media raises legal questions about its validity in terms of Islamic law. Based on the provisions of Article 65 of Law No. 7 of 1989 junto article 115 of the Compilation of Islamic Law (KHI) it is explained that divorce can only be carried out in front of a panel of judges in a court session. Divorce through social media reaps many pros and cons among scholars about its validity. Talaq through mobile electronic media either only in the form of sound or accompanied by its form in the form of pictures (video calls) in sharia talaq is declared as legal talaq, talaq is carried out via SMS, so scholars position this problem the same as the issue of divorce through writing. Meanwhile, according to the law on marriage in Indonesia, it is only declared valid if it is pronounced in a religious court.